A springs mapping exercise in Meghalaya - Kharsyntiew, Rose Christine M. (Technical Centre for Agricultural and Rural Cooperation, 2018)
The state of Meghalaya, in north east India, suffers from water shortages due to its hilly topography and the inability to store rain water. The Institute of Natural Resources in Shillong, under the Meghalaya Basin Development Authority, is carrying out springs mapping and springshed development initiatives to enhance the availability of water from the local springs, all of which are improving the situation for the local population.